2012
DOI: 10.1787/fmt-2011-5k9cswn0h042
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Framework for Effective Financial Crisis Management

Abstract: This article discusses the roles and responsibilities of the various agencies that are part of the financial system safety net, and it sets out a framework for the decision-making process for these actors in the management of a financial crisis. In this context, the article discusses issues of micro-and macro-prudential oversight and argues that more needs to be done to ensure accountability, independence, transparency and integrity of the various actors of the financial system safety net.JEL Classification: G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Future research ought to focus on short-term financial techniques that assist in reducing the impact of a recession. Previous studies have shown the importance of credit and risk management strategies that contribute to economic growth [6]. However, globalization has introduced new elements emanating from pandemic and subprime mortgages that require intensive measures.…”
Section: Future Researchmentioning
confidence: 99%
“…Future research ought to focus on short-term financial techniques that assist in reducing the impact of a recession. Previous studies have shown the importance of credit and risk management strategies that contribute to economic growth [6]. However, globalization has introduced new elements emanating from pandemic and subprime mortgages that require intensive measures.…”
Section: Future Researchmentioning
confidence: 99%
“…The crisis management carried out by the increasingly active central bank played a pivotal role in this process. 25 When Hungary was hit by the 2008 crisis, 26 it was vulnerable and defenceless. One reason for this, among others, was that the Constitution in force before 2011 did not contain any chapter on public finances; in other words, there was no constitutional rule, nor a guarantee enforcing compliance, for the limitation of excessive sovereign indebtedness.…”
Section: Outcomes Of Coordination In Hungarian Public Financesmentioning
confidence: 99%